EXPLORING THE ROLE OF LOCAL CHAMPION IN COMMUNITY-BASED RURAL HOMESTAY IN MALAYSIA: A CASE OF HOMESTAY SUNGAI HAJI DORANI - Abas, Siti Aisah; Abd Halim, Norhazliza; MOHD HANAFIAH, MOHD HAFIZ (Faculty of Built Environment and Surveying, 2021)
The homestay program is an essential driver for local community empowerment and distributed benefit individually or collectively. Most of the local communities in rural areas are encouraged to participate in this program due to their value-added income and platform to promote the local culture to tourists. However, incompetent leaders to lead Community-Based Rural Homestay (CBRH) become a challenge to homestay operators as they need a proactive leader to manage the activities and tourists at the same time. Poor leadership qualities affect the homestay program from being active in generating income and other benefits for the local community. Indeed, there is a need for the leader in a community project to act as the representative for the local community to guide them as the community may not be ready for the intended changes or development. Ten competencies were identified to explore the characteristics of local champions in the context of CBRH. A single case study has been used whereby this research was taken place at Homestay Sungai Haji Dorani. A mixed-method design is adopted in this research which is involved a questionnaire distributed to the homestay operators and the interview session with the local champion of Homestay Sungai Haji Dorani. The finding was revealed that fairness becomes a dominant competency of the local champion. In a nutshell, the local champion's role is crucial to facilitate the participation of the local community in tourism development. Furthermore, the local champion is also considered one of Malaysia's CBRH factor's internal success factors